Effects of interest rate caps on microcredit: Evidence from a natural experiment in Bolivia - María José Roa; Alejandra Villegas; Ignacio Garrón (Institute for Advanced Development Studies (INESAD), 2020)
This paper evaluates the imposition of caps on microcredit lending rates through directed credit policies for productive sectors. This financial inclusion intervention provides a unique quasi-experiment, allowing to estimate its causal effect following a difference-in-differences analysis. Our results suggest that the imposition of interest rate ceilings negatively affected the portfolio balance of new microcredits and loans to SMEs granted by MFIs. Particularly, we find robust results indicating that the balance of the microcredit and SME loans portfolio granted by MFIs, relative to the company portfolio granted by banks, decreased by 26.1% for an average MFI for the period 2011-2018.
Keywords: G18; G28; G38; 330; Interest rate ceilings; financial inclusion; credit access; microcredit loans; small and medium enterprises loans